FBI VS. AFRICAN AMERICANS (BASED ON COINTELPRO PROGRAM DOCUMENTS) - Zakirov Almaz Vasilovich (Вестник Брянского государственного университета)
Today we are witnessing how various US intelligence agencies are engaged in espionage activities around the world. However, US citizens have been subjected to the most sophisticated methods of persecution in history. Using the example of the FBI's COINTELPRO program (carried out from 1956 to 1971), directed against activists of the African-American civil rights movement, the article examines the FBI's activities to protect the socio-political foundations of American society, which cannot be called anything but segregational and racist. The author showed how the US government influenced key figures of the civil rights movement in the USA, such as Martin Luther King Jr., Malcolm X and activists of the Black Panthers party through the FBI COINTELPRO program. The consequences of the program are considered, including restrictions on civil liberties, trust in the government and institutional violation of the rights of African Americans. The relationship between the latter phenomenon and earlier phenomena of discrimination against the rights of the "Colored People" of the United States, such as abolitionism and seg-regation, is carried out. The article analyzes the impact of the FBI's COINTELPRO program on modern times, including its reflec-tion on modern legal norms, counterintelligence measures and public opinion about government surveillance. The study of the FBI's COINTELPRO program is important for understanding the complex relationship between government and civil society.